MORPHOLOGY AND HISTOCHEMISTRY OF ACUTE FATTY LIVER OF PREGNANCY DYSTROPHY - Erkin A. Eshbaev; Rajabboy I. Israilov; Xasan Z.Tursunov (Central Asian Journal of Medicine, 2022)
Morphology and histochemistry of acute fatty liver of pregnancy dystrophy (AFLPD), which is a rare, fatal liver damage, is a completely unexplored disease of etiology and pathogenesis. In this study, liver morphology and histochemistry have been studied in the case of HCV-infected patients in 2001-2020 years. In total, in 7 cases, the diagnosis of this disease is confirmed on the basis of specific clinical and morphological symptoms, some clinical symptoms are based on the results of a morphological examination of the liver.